The effectiveness of quality management interventions in reducing hospital-associated infections in adult patients: A systematic literature review - Arzu Hajiyeva; Johan Jarl; Sanjib Saha (International Journal of Infectious Diseases)
Background: This systematic literature review evaluates the effectiveness of Quality Management Tools (QMTs) in reducing Hospital-Associated Infections (HAIs) among adult inpatients in hospital settings. Methods: The systematic literature review, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline, systematically analyzed relevant studies from 2013 to 2023 across three electronic databases: PubMed, CINAHL, and EMBASE, using Covidence. The risk of bias assessment was performed using different validated tools depending on the study design. Results: The study encompassed 34 studies conducted in diverse healthcare settings worldwide. QMT interventions consisted of a total of 18 bundle interventions, five stewardship programs, four catheter usage interventions, three checklists, two audit and feedback interventions, and two oral care policies. Twenty-five studies showed significant decreases, whereas nine studies showed insignificant decreases in HAI rates after the deployment of QMTs. Although these interventions show promise, caution in interpretation is advised as only 6 of the included 34 studies had low risk of bias. The meta-analysis of seven studies on bundle interventions for ventilator-associated pneumonia (VAP), showed a 40% reduction in VAP incidence (OR: 0.40, 95% CI: 0.24-0.65; I² = 80.8%, P = 0.00). Conclusion: Introduction QMTs has the potential to reduce HAI among adult inpatients. Further research is warranted to optimize the implementation of QMTs to enhance patient care and public health outcomes.